Мемристоры для общественных действий и изменений (Вестник КазНУ. Серия Экономическая, 2022)
Within an information management domain, this conceptual paper provides and benefits from information on memristance/memristors and their possible applications into physical and social sciences in order to develop analogies among electrical, mechanical and social sciences to be used for an original and innovative model development for societal change and action. Possible implications such as utilization of social memristors for social movements, as well as development of artificial intelligence hardwares could be drawn from this work. This paper is a follow-up about the work on Circuits of Power in Quantum Organizations: Memristors for Post-Pandemic Consciousness in order to develop and suggest a new model of societal action benefiting from analogies among electrical sciences, mechanical sciences and social sciences. Accordingly this paper first gives background information on the related concepts of memristors and their possible applications into physical and social sciences. Benefiting from this background information, then, analogies among electrical, mechanical and social sciences will be used for a model development for societal change and action. A discussion for possible implications will also be provided, before the conclusion. Key words: memristor, societal action, artificial intelligence, information management